Differential functional theory and molecular docking studies of newly synthesized carbamates. Issue 11 (6th May 2019) - Danish, Muhammad; Raza, Muhammad A.; Anwar, Uzma; Rashid, Umer; Ahmed, Zaheer
Abstract : Four new carbamates (RZ1–RZ4) were synthesized from different amine moieties through reported methods. The reaction was monitored using thin layer chromatography and characterization was done using m.p., fourier‐transform infrared spectroscopy (FTIR), and X‐ray diffraction (XRD) techniques. Density functional theory (DFT) studies were carried out using Gaussian 09 software to compare the theoretical and practical parameters of the synthesized compounds. Highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) were also drawn to calculate the energy difference between orbitals. In‐vitro enzyme inhibition potential against acetylcholine esterase (AChE), butyrylcholine esterase (BChE), and protease was checked through standard protocols that suggested moderate inhibition against selected enzymes. Docking studies were also carried out, which depicted that these compounds have ability to bind on the active site of AChE and BChE. Abstract : A series of carbamates were prepared and their structure were elucidated using modern spectral techniques. Gaussian 09 was used for optimization and comparison of theoretical and practical parameters. HOMO and LUMO were also drawn to calculate the energy difference between orbitals. In‐vitro enzyme inhibition potential against acetylcholine esterase, butyrylcholine esterase, and protease was checked, which supported the docking results.